Suppression of NLRP3 Inflammasome by Dihydroarteannuin via the HIF‐1α and JAK3/STAT3 Signaling Pathway Contributes to Attenuation of Collagen-Induced Arthritis in Mice - Zhang, Mingying; Wu, Danbin; Xu, Jia; Liu, Lijuan; Jiao, Wei; Yu, Jiahui; Chen, Guangxing (Frontiers in Pharmacology, 2022)
Dihydroarteannuin (DHA), the primary of artemisinin extracted from the traditional Chinese herb Artemisia annua L., has been used in malaria treatment for a long time. Recently, many studies have indicated that DHA also exhibits potent anti-rheumatoid arthritis (RA) activity. In this study, collagen-induced arthritis (CIA) in DBA/1J mice and inflammatory model in THP-1 cells were established to evaluate the modulatory effects of DHA on joint destruction and to explore the underlying mechanisms. Our results showed that DHA decreased the serum levels of IL-1β and IL-6, alleviated paw oedema and reduced bone destruction in DBA/1J mice with CIA. Further exploration with inflammatory model in THP-1 cells indicated that DHA reduced the protein expression of hypoxia‐inducible factor (HIF)‐1α, and the phosphorylation in Janus kinase (JAK) 3 and signal transducer and activator of transcription (STAT) 3 protein, which resulted in a decrease of NOD-like receptor protein (NLRP) 3 expression and interleukin (IL)-1β release. Consequentially, the inflammatory activation in THP-1 cells was inhibited. Therefore, we concluded that DHA efficiently alleviated the inflammation and arthritic symptoms in CIA mice and downregulated inflammation in part by inhibiting NLRP3 expression via the HIF‐1α and JAK3/STAT3 signaling pathway. Thus, DHA may be considered as a potential therapeutic agent in RA treatment.